EVALUASI KUALITAS UDARA DAN DAMPAKNYA TERHADAP KESEHATAN PERNAFASAN PENDUDUK KOTA MEDAN - ALEXANDER PARLINDUNGAN MARPAUNG (JURNAL ILMIAH MAKSITEK, 2023)
Medan City As one of the cosmopolitan cities is a buffer of several cities outside Medan City, where Medan City has been densely populated and also dense traffic conditions, as well as on the outskirts of Medan City has emerged industry, where exposure to motor vehicle smoke and industrial smoke can make the weather in Medan City worse. During 2022, there were around 209 people affected by respiratory illness, 6,300 people exposed to penunomia, and there were around 3.2 million deaths due to respiratory illness caused by exposure to pollution or air pollution. The purpose of this study is to evaluate the air quality in Medan City and identify its potential impact on the respiratory health of Medan City residents, where poor air quality in urban areas can cause serious health problems, especially in the respiratory system. The purpose of this study is to evaluate the air quality in Medan City and identify its potential impact on the respiratory health of Medan City residents, where poor air quality in urban areas can cause serious health problems, especially in the respiratory system. This study uses an analytical descriptive method with a cross sectional approach. The number of respondents amounted to 75 people in several clinics and hospitals in Medan City, where data collection techniques were carried out using documentation studies, interviews with questionnaires and also by using observation. Data analysis techniques can be performed using the distribution of respondents, and Univariate analysis. Based on the results of the study, it can be concluded that the residents of Medan City who are vulnerable to respiratory health in the form of lung disorders or penunomia are in the age range of >60 years, as well as the source of respiratory health problems experienced by Medan City residents, then the source of respiratory problems experienced by Medan City residents is derived from motor vehicle smoke that contains high pollutants that can cause acute respiratory problems penunomia)